URGENSI PENDIDIKAN ANAK USIA DINI DALAM PERSPEKTIF PSIKOLOGI PENDIDIKAN : FONDASI PERKEMBANGAN KOGNITIF DAN EMOSIONAL ANAK - Muslim, Muslim (Kreatif: Jurnal Pemikiran Pendidikan Agama Islam, 2026)
Data analysis techniques were conducted qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that early childhood education at Al Mahasin PAUD is highly important in supporting children's cognitive and emotional development. Play-based learning, responsive teacher-child interactions, independence training, social activity integration, and the implementation of routine school activities have been proven to play a role in optimally shaping children's thinking skills, emotional regulation, and readiness to learn.